A novel nitronyl nitroxide radical HPN-C6 attenuates brain damage in an acute hypobaric hypoxia mouse model through inhibition of the oxidative stress. (21st June 2022) - Jing, Linlin; Huang, Yanru; Ma, Huiping; Wang, Haibo
Graphical abstract: A new efficient free radical scavenger HPN-C6 prevented brain damage induced by hypobaric hypoxia via reducing oxidative damage and inhibiting apoptosis and inflammatory response in mice brain. Highlights: The oxidant stress in mice brain induced by hypobaric hypoxia was inhibited by HPN-C6 . HPN-C6 increased the activities of antioxidant enzymes. HPN-C6 inhibited the occurrence of inflammatory reaction in mice brain. HPN-C6 suppressed the hypobaric hypoxia-induced apoptosis. Abstract: Hypobaric hypoxia (HH) results in the increased formation of ROS and induces a wide range of deleterious effects on the brain. Nitronyl nitroxide radicals are a kind of stable organic nitroxide radicals with a good ability to scavenge ROS. Herein, a series of new nitronyl nitroxide radicals was synthesized according to the previous method. Among them, a compound with six carbon atoms alkyl chain (HPN-C6 ) was screened for estimating the protective effect against HH-induced brain injury in the acute HH mouse model. The results showed that HPN-C6 ameliorated oxidative stress by decreasing the activity of LDH and the content of H2 O2, NO, and MDA, increasing the activities of SOD, CAT and GSH-PX in the brain tissue of HH injured mice. Moreover, HPN-C6 exhibited an anti-inflammatory effect by reducing the level of IL-1β, TNF-α, and IL-6 in the brains of mice after HH exposure through regulating the P38 MAPK signaling pathway. In addition, HPN-C6 exhibited the protection effect by inhibiting the release of mitochondrial cytochrome C, locking the activation of caspase-3, and downregulating the expression of Bax and upregulating the expression of Bcl-2. HPN-C6 pretreatment could inhibit the caspase-dependent mitochondria apoptosis pathway. These findings indicate that HPN-C6 is a potential therapeutic agent to prevent brain damage induced by HH.